The Effect of Acceptor and Donor Doping on Oxygen Vacancy Concentrations in Lead Zirconate Titanate (PZT) - Slouka, Christoph (Materials (Basel), 2016)
The different properties of acceptor-doped (hard) and donor-doped (soft) lead zirconate titanate (PZT) ceramics are often attributed to different amounts of oxygen vacancies introduced by the dopant. Acceptor doping is believed to cause high oxygen vacancy concentrations, while donors are expected to strongly suppress their amount. In this study, La(3+) donor-doped, Fe(3+) acceptor-doped and La(3+)/Fe(3+)-co-doped PZT samples were investigated by oxygen tracer exchange and electrochemical impedance spectroscopy in order to analyse the effect of doping on oxygen vacancy concentrations. Relative changes in the tracer diffusion coefficients for different doping and quantitative relations between defect concentrations allowed estimates of oxygen vacancy concentrations. Donor doping does not completely suppress the formation of oxygen vacancies; rather, it concentrates them in the grain boundary region. Acceptor doping enhances the amount of oxygen vacancies but estimates suggest that bulk concentrations are still in the ppm range, even for 1% acceptor doping. Trapped holes might thus considerably contribute to the charge balancing of the acceptor dopants. This could also be of relevance in understanding the properties of hard and soft PZT.